2021
DOI: 10.1186/s43008-021-00058-y
|View full text |Cite
|
Sign up to set email alerts
|

Quorum sensing-mediated inter-specific conidial anastomosis tube fusion between Colletotrichum gloeosporioides and C. siamense

Abstract: Many plant pathogenic filamentous fungi undergo fusion of conidia through conidial anastomosis tubes (CATs), which is believed to facilitate horizontal gene transfer between species. We discovered a remarkable inter-specific CAT fusion between two important plant fungal pathogens Colletotrichum gloeosporioides and C. siamense. In an invitro assay, under no selection pressure, the inter-specific CAT fusion was preferred with higher frequency (25% ± 5%) than intra-specific CAT fusion (11% ± 3.6%). Different stag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…The heterokaryotic progenies have been generated through CAT fusion with distinct phenotypes compared to parental strains in F. oxysporum and C. lindemuthianum [9,13]. Inter-specific CAT fusion between C. lindemuthianum and C. gossypii resulted in the formation of some hybrids, which exhibited phenotypic variations; one hybrid was highly pathogenic [14] Furthermore, we have demonstrated that an inter-specific CAT fusion between C. gloeosporioides and C. siamense generated genetic and phenotypic diversity in these fungal pathogens [11]. Pathogen populations with higher genetic variations tend to show increased mean fitness, resilience, expansion of host range, and fungicide resistance.…”
Section: Introductionmentioning
confidence: 89%
See 4 more Smart Citations
“…The heterokaryotic progenies have been generated through CAT fusion with distinct phenotypes compared to parental strains in F. oxysporum and C. lindemuthianum [9,13]. Inter-specific CAT fusion between C. lindemuthianum and C. gossypii resulted in the formation of some hybrids, which exhibited phenotypic variations; one hybrid was highly pathogenic [14] Furthermore, we have demonstrated that an inter-specific CAT fusion between C. gloeosporioides and C. siamense generated genetic and phenotypic diversity in these fungal pathogens [11]. Pathogen populations with higher genetic variations tend to show increased mean fitness, resilience, expansion of host range, and fungicide resistance.…”
Section: Introductionmentioning
confidence: 89%
“…To study the effect of conidial age on GT formation and CAT fusion and their mutual exclusiveness in C. gloeosporioides, the GT and CAT induction assays were carried out by following a protocol developed in our lab [11]. The C. gloeosporioides (CBS 953.97) culture was inoculated on bean pod agar medium (autoclaved French bean pods submerged in 2% water agar) and was incubated in the dark at 25 • C to induce conidiation.…”
Section: In Vitro Dynamics Of Gt Formation and Cat Fusionmentioning
confidence: 99%
See 3 more Smart Citations